Evaluation Of Treatment Outcomes, Factors Affecting Treatment Defaulting And Health Related Quality Of Life Of Newly Diagnosed Tuberculosis Patients In Yemen - Jaber, Ammar Ali Saleh (2018)
Despite the effectiveness of tuberculosis (TB) treatment, TB remains the most challenging infectious disease worldwide due to augmented trend of mortality and morbidity. In addition, in Yemen, TB consider as the 4th causes of death. Presentstudy is designed to evaluates TB among smear positive pulmonary tuberculosis (PTB) including treatment outcome, health related quality of life (HRQoL) and risk factors associated with TB defaulters. A prospective cohort study was designed. The study conducted in two high TB prevalent cities (Taiz and Al Hudaydah) of Yemen, between April 2014 and January 2016. Moreover, this study reported a lower success rate of 83% compare to WHO target of 85%.